Global secularity / Volume 1 Mapping the academic debate / edited by Johannes Duschka, Christoph Kleine, Monika Wohlrab-Sahr, and Florian Zemmin - Duschka, Johannes; Kleine, Christoph; Wohlrab-Sahr, Monika; Zemmin, Florian (Global secularity a sourcebook, 2024)
This volume maps the international academic debate on secularity. It places seminal contributions from within 'Western' academia alongside less well-known texts from various parts of the world; in several cases this is the first time that they have been translated into English. The volume demonstrates that the academic debate on secularity was and is a global debate, with contributions from many regions. The collected texts relate to each other either directly or indirectly by referring to similar arguments - whether reinforcing or criticising them - and thus create a discourse. When speaking of global secularity, we therefore do not insinuate a uniform 'world secularity' resulting from the alleged global diffusion of 'Western' norms, ideas and concepts. It is rather a web of relations that is constituted via various different references. These references are not evenly distributed: the development in 'the West' is often the point of reference to which positions from other regions relate, to which they connect, or from which they distance themselves. But the references are not completely unidirectional: We also present texts from Europe that underline the multidirectionality of the process, even early on. Thereby, the volume offers the reader the material with which to trace these global exchanges and references